Pengendalian Kimia dan Resistensi Vektor Anopheles Dewasa pada Kawasan Endemis Malaria di Dunia - Musfirah, Musfirah (Universitas Ahmad Dahlan, 2017)
Background: Various methods of malaria vector control has been done. Insecticides which using repeatedly impact new problems for the emergence of vector resistance. Hence, optimizationÂ about active ingredientÂ in the insecticideÂ productÂ should take noticeÂ toÂ the developmentÂ ofÂ insecticide resistanceÂ mechanisms forÂ malariaÂ vectors. Literature review whichÂ assess and discussÂ adult Anopheles sp resistanceÂ forÂ chemical control programmeÂ wereÂ still limited to certain insecticides. The aimÂ ofÂ thisÂ literature review isÂ collecting andÂ findingsÂ evidence has been producedÂ by researchers whichÂ associatedÂ withÂ chemical control ofÂ vectorÂ andÂ Â varietyÂ ofÂ adultÂ Anopheles resistanceÂ asÂ aÂ strategyÂ to eradicate malaria endemic cases. Method: This literature review prepared by systematic review methods.Google database is used as the primary source of search with keyword